Melatonin mitigates oxidative damage induced by anthracycline: a systematic-review and meta-analysis of murine models - Faggiano, Andrea; Gherbesi, Elisa; Avagimyan, Ashot; Ruscica, Massimiliano; Donisi, Luca; Fedele, Maria Antonia; Cipolla, Carlo Maria; Vicenzi, Marco; Carugo, Stefano; Cardinale, Daniela (Frontiers in Cardiovascular Medicine, 2023)
Background Oxidative stress induced by the excessive production of reactive oxygen species is one of the primary mechanisms implicated in anthracycline (ANT)-induced cardiotoxicity. There is a strong clinical need for a molecule capable of effectively preventing and reducing the oxidative damage caused by ANT. In vitro and in vivo studies conducted in mice have shown that melatonin stimulates the expression of antioxidative agents and reduces lipid peroxidation induced by ANT. Methods We investigated this issue through a meta-analysis of murine model studies. The outcome of the meta-analysis was to compare oxidative damage, estimated by products of lipid peroxidation (MDA = Malondialdehyde) and markers of oxidative stress (SOD = Superoxide Dismutase, GSH = Glutathione), along with a marker of cardiac damage (CK-MB = creatine kinase–myocardial band), assessed by measurements in heart and/or blood samples in mice undergoing ANT chemotherapy and assuming melatonin vs. controls. The PubMed, OVID-MEDLINE and Cochrane library databases were analysed to search English-language review papers published from the inception up to August 1st, 2023. Studies were identified by using Me-SH terms and crossing the following terms: “melatonin”, “oxidative stress”, “lipid peroxidation”, “anthracycline”, “cardiotoxicity”. Results The metanalysis included 153 mice administered melatonin before, during or immediately after ANT and 153 controls from 13 studies. Compared with controls, the levels of all oxidative stress markers were significantly better in the pooled melatonin group, with standardized mean differences (SMD) for MDA, GSH and SOD being −8.03 ± 1.2 (CI: −10.43/−5.64, p < 0.001), 7.95 ± 1.8 (CI: 4.41/11.5, p < 0.001) and 3.94 ± 1.6 (CI: 0.77/7.12, p = 0.015) respectively. Similarly, compared with controls, CK-MB levels reflecting myocardial damage were significantly lower in the pooled melatonin group, with an SMD of −4.90 ± 0.5 (CI: −5.82/−3.98, p < 0.001). Conclusion Melatonin mitigates the oxidative damage induced by ANT in mouse model. High-quality human clinical studies are needed to further evaluate the use of melatonin as a preventative/treatment strategy for ANT-induced cardiotoxicity.